2014
DOI: 10.1093/jjco/hyu022
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Longitudinal Study Profile and Distress of Couples in Relation to the Conduct of Prostate Biopsy

Abstract: Objective: Partners of prostate cancer patients have been reported to suffer from high levels of psychological distress, although there are few reports of the changes in their distress levels observed before and after the diagnosis and the factors influencing them. This study constructed a longitudinal psychosocial database of prostate cancer biopsy subjects and their partners. This paper describes a summary of the database and the nature and severity of the psychological distress and cancer-related worry. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…However, men whose partners had cancer with pain did have a higher risk of psychological distress, whereas men whose partners had cancer but no pain did not show a higher risk. Earlier studies showed that participants whose partners have cancer were more likely to have negative psychological symptoms such as depression and anxiety (Kornblith et al 1994;Toseland et al 1995;Nijboer et al 2001;Baider et al 2003;Bishop et al 2007;Rhee et al 2008;Sjovall et al 2009;Nakaya et al , 2016bMoser et al 2013;Oba et al 2014). Thus, our results differ from those of these earlier studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, men whose partners had cancer with pain did have a higher risk of psychological distress, whereas men whose partners had cancer but no pain did not show a higher risk. Earlier studies showed that participants whose partners have cancer were more likely to have negative psychological symptoms such as depression and anxiety (Kornblith et al 1994;Toseland et al 1995;Nijboer et al 2001;Baider et al 2003;Bishop et al 2007;Rhee et al 2008;Sjovall et al 2009;Nakaya et al , 2016bMoser et al 2013;Oba et al 2014). Thus, our results differ from those of these earlier studies.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that spouse's hospitalization greatly contributed to the risk of mortality in both men and women, making it clear that the hospitalization of a spouse has serious adverse health effects. Furthermore, there have been many epidemiological studies on the mental problems of partners of cancer patients (Kornblith et al 1994;Toseland et al 1995;Nijboer et al 2001;Baider et al 2003;Bishop et al 2007;Rhee et al 2008;Sjövall et al 2009;Nakaya et al , 2016bMoser et al 2013;Oba et al 2014). Nakaya et al (2010) reported that men whose partners were diagnosed with breast cancer had an increased risk of being hospitalized with an affective disorder, and the risk showed a dose-response relationship with the severity of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with early‐stage prostate cancer have a 99% 5‐year survival rate (American Cancer Society, ). Nevertheless, a confirmed diagnosis of prostate cancer psychologically affects not only people but also their spouses (Chien, Chuang, Liu, Huang, & Liu, ; Chien et al., ; Lehto, Aromaa, & Tammela, ; Tanner, Galbraith, & Hays, ), including their having concerns about prostate disease, side effects and complications of treatment, death from prostate cancer and cancer recurrence during the disease process (Oba et al., ; Tanner et al., ; van de Wal et al., , ), more so for spouses of people with prostate cancer than people with cancer themselves (Oba et al., ). Further, the suicide rate of newly diagnosed people with cancer is 2.47 times higher than that of the general population (Lin et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…complications of treatment, death from prostate cancer and cancer recurrence during the disease process (Oba et al, 2014;Tanner et al, 2011;van de Wal et al, 2016van de Wal et al, , 2017, more so for spouses of people with prostate cancer than people with cancer themselves (Oba et al, 2014). Further, the suicide rate of newly diagnosed people with cancer is 2.47 times higher than that of the general population (Lin et al, 2017).…”
mentioning
confidence: 99%